Mechanical properties of lithium slag recycled aggregate concrete subject to high temperature. - Jiongfeng Liang; Ying Yang; Caisen Wang; Ziyi Hu; Wei Li (PLoS ONE)
In attempting to enhance the mechanical properties of recycled concrete after high temperature and solve the problem of large stacking of lithium slag (LS), this paper proposes lithium slag recycled concrete (LSRAC). In this research, LS was used to replace part of the cement (γL = 10%, 20%, and 30%), recycled coarse aggregate (RCA) completely replaced the natural aggregate (γR = 100%), and the heated temperatures were 200°C, 400°C, and 600°C. This paper carried out the heating test and the strength tests. The test results indicated, for the same heating temperature, the loss of strength of LSRAC was less than that of RAC and the compressive strengths and splitting strength of LSRAC with 20% lithium slag replacement rate were improved by 33.9%, 36.5% and 34.5%, respectively. The increase in flexural strength of LSRAC with 10% lithium slag dosage reached 24.1%. The results indicate LSRAC can effectively improve the bearing capacity of structural concrete subject to high temperature. The strength retention equations of LSRAC were established by comparing the strengths of 20°C. The calculation results of the strength retention formula for post-high-temperature LSRAC matched the measured results well. Therefore, this paper provided reliable experimental basis and theoretical guidance for on-site rescue, post-disaster assessment and reinforcement of RAC used for pavement base and public facilities constructions, and the eco-friendly way for sustainable development.